DETERMINANT FACTORS INFLUENCING NURSING RESILIENCE ON NURSING WORK EFFICIENCY AT KING FAHAD SPECIALIST HOSPITAL – QASSIM CLUSTER 2026 - Hanan Saad A; Alayed Alayed; Hafizah Che Hasan (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The complexity of modern healthcare services has led nursing personnel to face high workloads, intensive emotional demands, and dynamic, high-risk working environments. These conditions make nursing resilience an essential psychological factor in maintaining the effectiveness and efficiency of nursing performance. This study aimed to analyze the determinant factors influencing nursing resilience and its impact on nursing work efficiency at King Fahad Specialist Hospital in 2026. This study employed a quantitative cross-sectional design using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The study population consisted of all active nurses at the Qassim Health Cluster, totaling 4,425 nurses. A total of 356 respondents were selected using stratified random sampling. Data were collected using the Nursing Resilience Scale, Nursing Work Efficiency Scale, Utrecht Work Engagement Scale, and Perceived Organizational Support Scale, all of which had been tested for validity and reliability. Data analysis was conducted using SmartPLS 4. The results showed that organizational support (β = 0.431; p < 0.001), work engagement (β = 0.388; p < 0.001), psychological well-being (β = 0.362; p < 0.001), and a supportive work environment (β = 0.295; p < 0.001) had significant positive effects on nursing resilience. Conversely, high workload negatively affected nursing resilience (β = -0.276; p < 0.001). Nursing resilience was also found to have a significant positive effect on nursing work efficiency (β = 0.614; p < 0.001). The R-square value of 0.71 indicated that the research model explained 71% of the variance in nursing work efficiency. Nursing resilience is a strategic psychological resource influenced by organizational, psychological, and work environment factors in improving nursing work efficiency. This study is expected to provide theoretical contributions to the development of nursing management and healthcare organizational behavior literature, as well as practical contributions for hospitals in designing strategies to strengthen healthcare workers’ psychological resilience based on human-centered healthcare management.